The question is :

Let $R$ be a Dedekind domain and $I,J$ be fractional ideals in $R$. Then $I \cong J$ as $R-$modules if and only if $IJ^{-1}$ is a principal ideal of the quotient field $K(R)$ of $R$ i.e. $[I]=[J]$ in the class group $C(R)$.

The hint given was in one direction : if $\phi : I \to J$ is an isomorphism, then I must show that $\frac{\phi(a)}a$ is constant (doesn't depend on $a$).

In the reverse direction , if $IJ^{-1} = (c)$ for some $c \in K(R)$, then since $I$ is fractional and $R$ is Dedekind, $I = \frac{(a,b)}r$ for some $r$, since every ideal is doubly generated in a Dedekind domain, and similarly for $J$. How does this give me an isomorphism?

In the forward direction, if we assume first that $I,J$ are integral (i.e. ideals of $R$ itself) then pick $a \in I$ and note that ,$\phi : I \to J$ induces $\phi_m : S_m^{-1}I \to S_m^{-1} J$ (the localizations of $I$ and $J$ at every maximal ideal $m$, particularly those $m_i$ which contain $a$). Now, $S_{m_i}^{-1}(a)$ is mapped to some $S_{m_i}^{-1}(b)$ since $S_m^{-1}R$ is a discrete valuation ring. But I am not able to bring in $\frac{\phi(a)}a$ anywhere : how do I bring the quotient in, in the first place?


Assume that $[I]=[J]$. Then we know that $\exists a,b \in R$ s.t. $(a)I = (b)J$. In particular for $x \in I$ there exists unique $y \in J$ s.t. $ax = by$. Now define a map $\phi: I \to J$ by sending $x$ to $y$. As mentioned above this map is a bijection and we only need to prove that $\phi$ is a module homomorphism. Now we have that if $ax_1 = by_1$ and $ax_2 = by_2$ then $a(x_1+x_2) = b(y_1+y_2)$. This means that:

$$\phi(x_1 + x_2) = y_1 + y_2 = \phi(x_1) + \phi(x_2)$$

Also if $r \in R$, then if $ax = by$ we have that $a(rx) = b(ry)$. Thus we have that:

$$\phi(rx) = ry = r\phi(y)$$

This finishes the first direction.

For the other side I have a proof that doesn't make use of the hint. Let $\phi: I \to J$ be an $R$-module isomorphism. Then $\exists r,k \not = 0 \in R$ s.t. $rI \subseteq R$ and $kJ \subset R$, as $I$ and $J$ are fractional ideals. Now it's not hard to see that the restriction of $\phi$ to $rkI$ is an isomorphism between $(rk)I$ and $(rk)J$, which are both integral ideals.

Indeed $\phi(rkx) = rk\phi(x) = rky$ and the bijectivity isn't hard to proof. Now we'll prove that for a fixed $x \in (rK)I$ we have $\phi(x)(rk)I = x(rk)J$. This follows as:

$$\phi(x)(rk)a = \phi(xrka) = x\phi(ra) = xrk\phi(a) \in xrkJ \implies \phi(x)rkI \subset xrkJ$$ $$xrkb = xrk\phi(a) = \phi(xrka) = \phi(x)rka \in \phi(x)rkI \implies xrkJ \subset \phi(x)rkI$$

Note that in the first line we used the fact that $rka \in R$ to put it inside the isomorphism. While in the second line we used the surjectivity of $\phi$ to get that for every $b \in j$ there is $a \in I$ s.t. $\phi(a) = b$.

So as $x \in (rk)I \subset R$ and $\phi(x) \in (rk)J \subset R$ we get that $(rk)I \sim (rk)J$. Thus we have that $[(rk)I]=[(rk)J] \implies [(rk)][I] = [(rk)][J] \implies [I]=[J]$. Hence the proof.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.